Women's Contribution to Preventing Adolescent Reproductive Health Risks Through Family and Community Education - Rukayati (Journal Discrimination and Injustice, 2025)
This study aims to measure women's contribution in preventing adolescent reproductive health risks through family and community education in Lampung Province. Housewives and adolescent girls (aged 15 to 19 years) were 120 respondents in this quantitative study using a correlational survey strategy. A closed-ended Likert scale survey was used to collect data, which were then analyzed using simple linear regression and Pearson correlation. The findings indicate that there is a strong correlation between the amount of women's involvement in family education and the level of reproductive health knowledge among adolescents. This study adopts the mubadalah perspective as a conceptual framework, to review the structure of gender relations in mutual value-based education, which has not been the main focus in conventional reproductive health education approaches. Thus, the results of this study are expected to be the basis for developing a more contextual and inclusive educational intervention model for local and religious values ​​in adolescent reproductive health issues